The role of the dorsomedial hypothalamus in the cardiogenic sympathetic reflex in the Sprague Dawley rat - Zahner, Matthew R.; Hillard, Kynlee J.; Chandley, Michelle C. (Frontiers in Physiology, 2024)
Myocardial ischemia causes the production and release of metabolites such as bradykinin, which stimulates cardiac spinal sensory afferents, causing chest pain and an increase in sympathetic activity referred to as the cardiogenic sympathetic afferent reflex. While the brain stem nuclei, such as the nucleus tractus solitarius and rostral ventrolateral medulla, are essential in the cardiogenic sympathetic afferent reflex, the role of other supramedullary nuclei in the cardiogenic sympathetic afferent reflex are not clear. The dorsomedial hypothalamic nucleus (DMH) is involved in cardiovascular sympathetic regulation and plays an important role in the sympathetic response to stressful stimuli. In this study, we determined the role of DMH in the cardiogenic sympathetic afferent reflex. To do this we measured arterial pressure, heart rate, and renal sympathetic nerve activity (RSNA) responses to epicardial bradykinin (10 μg/mL) in anesthetized Sprague Dawley rats before and after bilateral DMH microinjection (50 nL) of either the GABAA agonist muscimol (0.5 nmol) to inhibit or the antagonist bicuculline (40 pmol) to disinhibit activity. Muscimol inhibition elicited a modest, albeit significant, reduction in basal arterial pressure and heart rate and attenuated the arterial pressure and heart rate reflex response to epicardial bradykinin. However, it did not change the magnitude of the reflex. Bicuculline disinhibition of the DMH increased basal arterial pressure, heart rate, and RSNA but did not augment the response to epicardial bradykinin. These results suggest that sympathetic activity derived from the DMH does not play an important role in the cardiogenic sympathetic afferent reflex in Sprague Dawley rats.